USING FLASHCARDS TO MOTIVATE STUDENTS TO LEARN ENGLISH AT SDN KARANGAYU 03 SEMARANG - Ade Winda Rahmawati; Katharina Rustipa (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This article discussed students' motivation to learn English using flashcards, especially for learning English Speaking, which focused on fluency and pronunciation. From the various problems regarding student motivation in the learning process, Flashcard is a media that is quite effective for teaching first-grade elementary school students because young learners still like to learn while playing. The data source came from observation and interviews with the English teacher and first-grader students at SDN Karangayu 03 Semarang. From the teacher's perspective: (1) Fun; (2) Effective; (3) Students easily understand the material taught because young learners learn while playing. From the students' perspective: (1) Learning with flashcards is fun and engaging; (2) The students all are happy learning using flashcards; (3) Didn't feel bored; (4) Want to learn using flashcards again in the future. So, it concluded that learning English Speaking using flashcards has a good impact and can motivate students to learn.